THE RELATIONSHIP BETWEEN EMPLOYEE ENGAGEMENT, ORGANIZATIONAL CULTURE, AND ORGANIZATIONAL COMMITMENT TOWARDS EMPLOYEE PERFORMANCE AT PT PUPUK ISKANDAR MUDA - Yulia Hafidzah Sinaga; Likdanawati; Faisal Matriadi; Ibrahim Qamarius (RADJA PUBLIKA, 2025)
This study aims to analyze the relationship between employee engagement, organizational culture, and organizational commitment on employee performance at PT Pupuk Iskandar Muda. The research employed a quantitative approach using a survey method through questionnaires distributed to selected employees. Data were analyzed using multiple linear regression to examine both partial and simultaneous effects among variables. The results show that employee engagement has a positive and significant effect on employee performance. Organizational culture also has a positive and significant impact on improving performance. Furthermore, organizational commitment plays an important role in enhancing optimal performance. Simultaneously, the three variables have a positive and significant influence on employee performance, indicating that higher levels of engagement, culture, and commitment lead to better employee performance. This study is expected to provide valuable insights for the management of PT Pupuk Iskandar Muda in formulating strategies to improve performance through strengthening employee engagement, developing organizational culture, and enhancing organizational commitment.